A Report of Health Related Anthropometric Indices in 2–5 Years Old Children of Golestan Province of Iran in 2015 - Jalali, Arefe Khaksar (Clin Nutr Res, 2019)
Pediatric malnutrition is an enormous health issue all around the world and its distribution is different in distinct areas of a country. This study has been designed to report the anthropometric status and some socio-economic factors among 2–5 years old children from Golestan province of Iran to show a better view of pediatric health status and better planning for future actions. This study was carried out by clustered-randomized sampling method on 1,382 of 2–5 years old children in urban and rural areas of Golestan province. Anthropometric measurements were performed and World Health Organization child growth standards were used for further analyses. The prevalence of stunting in boys and girls were 7.4% and 7.5% in urban and 4.1% and 5.4% in rural areas. The prevalence of underweight in boys and girls were 6.9% and 4.7% in urban and 5.7% and 4.4% in rural areas. The prevalence of subjects being at risk for overweight were 17.8% and 11.7% in boys and girls, respectively, in urban areas and were 11.1% and 9.2% in rural areas, respectively. There was a marginally significant difference between urban boys and girls in terms of weight status (p = 0.067). In this study remarkably high prevalence of malnutrition, especially a high dominance of overweight, was reported in Golestan province of Iran. Follow-up investigation to identify the cause of malnutrition and to establish public health policies are needed to revise these health issues in Golestan province of Iran.